The role of TRP proteins in mast cells - Freichel, Marc; Almering, Julia; Tsvilovskyy, Volodymyr (Frontiers in immunology, 2012)
TRP proteins form cation channels that are regulated through strikingly diverse mechanisms including multiple cell surface receptors, changes in temperature, in pH and osmolarity, in cytosolic Ca2+ concentration ([Ca2+]i) and by phosphoinositides. The 28 TRP proteins identified in mammals are classiﬁed into 6 subfamilies: TRPC, TRPV, TRPM, TRPA, TRPML, and TRPP. When activated, they contribute to cell depolarization and Ca2+ entry, which makes them polymodal sensors for fine tuning of many cellular and systemic processes in the body. In mast cells, the increase of [Ca2+]i is fundamental for their biological activity, and several entry pathways for Ca2+ and other cations were described including Ca2+ release activated Ca2+ channels (CRAC). Like in other nonexcitable cells, TRP channels could directly contribute to Ca2+ influx via the plasma membrane as constituents of Ca2+ conducting channel complexes or indirectly by shifting the membrane potential and regulation of the driving force for Ca2+ entry through independent Ca2+ entry channels. Here, we summarize the current knowledge about the expression of individual Trp genes with the majority of the 28 members being yet identified in different mast cell models, and we highlight mechanisms how they can regulate mast cell functions. Since specific agonists or blockers are still lacking for most members of the TRP family, studies to unravel their function and activation mode still rely on experiments using genetic approaches and transgenic animals. RNAi approaches suggest a functional role for TRPC1, TRPC5 and TRPM7 in mast cell derived cell lines or primary mast cells, and studies using Trp gene knock out mice reveal a critical role for TRPM4 in mast cell activation and for mast cell mediated cutaneous anaphylaxis, whereas a direct role of cold- and menthol-activated TRPM8 channels seems to be unlikely for the development of cold urticaria at least in mice.
Gesehen am 30.04.2018